LA PLANIFICACION MICROCURRICULAR DE LA CARRERA DE INDUSTRIA DEL VESTIDO Y SU RELACION CON EL PERFIL DE EGRESO DE LA BACHILLER TECNICA EN EL INSTITUTO TECNOLOGICO BABAHOYO - MARITZA GALLEGOS ZURITA (2005)
THE MICROCURRICULAR PLANNING OF THE CAREER IN THE CLOTHING INDUSTRY AND ITS RELATIONSHIP WITH THE GRADUATION PROFILE OF THE TECHNICAL BACHELOR'S DEGREE AT THE BABAHOYO INSTITUTE OF TECHNOLOGY